PELAKSANAAN PEMBERIAN BANTUAN HUKUM TERHADAP MASYARAKAT TIDAK MAMPU DI LUAR PENGADILAN (NON-LITIGASI) - Effendi, Devirianti (UNES Journal of Swara Justisia, 2018)
Given the importance of legal aid in creating justice, upholding human rights and equality before the law, as well as in achieving due process of law, the obligation of providing legal aid becomes essential to be effectively implemented. This research is very important, given the enormous benefits that will be gained when the implementation of legal assistance to the community can not be outside the court , can be implemented effectively, but also provides a form of legal reform effort in the aspect of equity distribution.